2022
DOI: 10.1007/s10554-022-02724-7
|View full text |Cite
|
Sign up to set email alerts
|

Machine learning evaluation of LV outflow obstruction in hypertrophic cardiomyopathy using three-chamber cardiovascular magnetic resonance

Abstract: Left ventricular outflow tract obstruction (LVOTO) is common in hypertrophic cardiomyopathy (HCM), but relationships between anatomical metrics and obstruction are poorly understood. We aimed to develop machine learning methods to evaluate LVOTO in HCM patients and quantify relationships between anatomical metrics and obstruction. This retrospective analysis of 1905 participants of the HCM Registry quantified 11 anatomical metrics derived from 14 landmarks automatically detected on the three-chamber long axis … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 33 publications
0
3
0
Order By: Relevance
“…Interestingly, a recent retrospective study applying machine learning algorithms in a large dataset of HCM patients with available cardiac magnetic resonance imaging reported concordant results. 28 They found that among several anatomical parameters, distance between anterior mitral valve leaflet tip and basal septum best predicted presence of resting LVOTO. Our study further extends these findings involving also patients with provocable LVOTO and providing an easily applicable echocardiographic parameter.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, a recent retrospective study applying machine learning algorithms in a large dataset of HCM patients with available cardiac magnetic resonance imaging reported concordant results. 28 They found that among several anatomical parameters, distance between anterior mitral valve leaflet tip and basal septum best predicted presence of resting LVOTO. Our study further extends these findings involving also patients with provocable LVOTO and providing an easily applicable echocardiographic parameter.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, we have made available for the clinical and scientific community such metrics in the form of a web service (hosted at the Cardiac Atlas Project, www.cardiacatlas.org ). Although recent work has shown the potential of simpler metrics derived from three-chamber longitudinal views of the heart for the assessment of LVOTO in HCM, 36 our 3D analysis provides more information and can be similarly integrated into the clinical workflow in a fully automated manner. There is an opportunity to explore the assessment of the presented 3D LV phenotypes with data already available in current clinical practice.…”
Section: Discussionmentioning
confidence: 99%
“…Multimodality imaging is essential in confirming the diagnosis of HCM, the presence of LV outflow tract obstruction (LVOTO), and risk stratification for sudden cardiac death [4]. Machine learning evaluation of LV wall thickness and LVOTO is evolving [5,6].…”
Section: Introductionmentioning
confidence: 99%